Feed Engineering for Sustainable Livestock Nutrition - Shah, Syed Muhammad Ali (Department of Agro-industrial Technology, University of Brawijaya, 2025)
AbstractFeed Engineering integrates mechanical, biological, and chemical processes to enhance nutrient efficiency and sustainability in animal production. This study aimed to synthesize recent evidence on key feed engineering technologies (pelleting, grinding, fermentation, and agro-industrial by-product valorization) through a systematic literature review following the PRISMA 2020 framework. From 642 publications initially identified, 97 met the final inclusion criteria. Results reveal that optimized pelleting and grinding improved feed conversion ratios by 6–12%, nutrient digestibility by up to 15%, and reduced methane emissions by 10–15%, depending on livestock species and processing parameters. Incorporation of residues such as cassava pulp, rice bran, and fruit pomace lowered feed costs by around 15% and improved waste utilization efficiency by 18%. Biological and enzymatic treatments further enhanced protein solubility and detoxified antinutritional compounds, increasing the safety and nutritional value of formulated feeds. These integrated processes demonstrate that Feed Engineering not only boosts productivity but also contributes to circular resource use and emission reduction. Future developments should focus on establishing standardized processing parameters, ensuring long-term feed safety, and integrating digital process control for precision and energy efficiency, enabling sustainable and climate-resilient livestock systems.Keywords: Feed engineering, livestock nutrition, pelleting, agro-industrial by-products, sustainability AbstrakRekayasa Pakan (Feed Engineering) mengintegrasikan proses mekanis, biologis, dan kimiawi untuk meningkatkan efisiensi dan keberlanjutan nutrisi dalam produksi ternak. Studi ini bertujuan untuk mensintesis bukti terkini tentang teknologi rekayasa pakan utama (pelet, penggilingan, fermentasi, dan valorisasi produk sampingan agroindustri) melalui tinjauan pustaka sistematis yang mengikuti kerangka kerja PRISMA 2020. Dari 642 publikasi yang awalnya diidentifikasi, 97 memenuhi kriteria inklusi akhir. Hasil penelitian menunjukkan bahwa pelet dan penggilingan yang dioptimalkan meningkatkan rasio konversi pakan sebesar 6–12%, daya cerna nutrisi hingga 15%, dan mengurangi emisi metana sebesar 10–15%, tergantung pada spesies ternak dan parameter pengolahan. Penambahan residu seperti ampas singkong, dedak padi, dan ampas buah menurunkan biaya pakan sekitar 15% dan meningkatkan efisiensi pemanfaatan limbah sebesar 18%. Perlakuan biologis dan enzimatik semakin meningkatkan kelarutan protein dan mendetoksifikasi senyawa antinutrisi, sehingga meningkatkan keamanan dan nilai gizi pakan yang diformulasikan. Proses-proses terintegrasi ini menunjukkan bahwa Rekayasa Pakan tidak hanya meningkatkan produktivitas tetapi juga berkontribusi pada pemanfaatan sumber daya secara sirkular dan pengurangan emisi. Pengembangan di masa mendatang harus berfokus pada penetapan parameter pemrosesan yang terstandarisasi, memastikan keamanan pakan jangka panjang, dan mengintegrasikan kontrol proses digital untuk presisi dan efisiensi energi, yang memungkinkan sistem peternakan yang berkelanjutan dan tangguh terhadap iklim.Keywords: Rekayasa pakan, nutrisi ternak, pelet, produk sampingan agroindustri, keberlanjutan